Graduate employability and educational context: a comparison between Great Britain and the Netherlands. (29th November 2012) - Tholen, Gerbrand
<x xml:space="preserve">Abstract</x> Within policy circles, graduate employability remains a problem. It is often understood as an individual phenomenon, overlooking the influence of the organisation of higher education on the competition for graduate jobs. This article explores and compares how graduate employability is socially constructed within Great Britain and the Netherlands. It provides an analysis of both Dutch and British systems of higher education and explains how they shape the positional competition for graduate jobs. In addition it shows how perceptions of employability of final year university students relate to these two educational systems. The article is based on an empirical study on graduate employability in both countries using both micro analysis as well as contextual analysis. The article shows a fit between educational structure and employability strategies. The educational context shapes graduates' understandings and expectations of the competition for graduate jobs.